Code-Switching in “Kongsi Raya”: Unveiling Communication Patterns in Cinema - Kanasan, Muthukumaran; Hou, Edmund Ngo Chun (Integrated Journal for Research in Arts and Humanities, 2024)
Code-switching, a prevalent phenomenon in societies, especially among multilingual individuals, involves effortlessly transitioning between languages. Some scholars argue that code-switching signals a lack of language proficiency, while others believe it is an additional tool for achieving specific interactive goals when conversing with others. This behavior is not limited to real-life interactions but also appears in various creative mediums such as talk shows, music, films, and other artistic expressions. The primary objective of this research was to identify and analyze instances of code-switching in the film "Kongsi Raya." Using a qualitative descriptive methodology, the study collected and thoroughly examined selected scenes and dialogues from the movie, applying Malik's (1994) code-switching functions framework. The findings showed that code-switching was used either unconsciously or deliberately as an essential communication strategy to effectively convey the speakers' intended meaning, including emotions or simply providing information. This behavior reflects real-life communication scenarios in a culturally diverse country like Malaysia.